MOTIF BERMAIN GAME ONLINE STUDI KASUS PADA REMAJA DESA SUMBERSARI BANYUWANGI - Agung Obiyanto; Muhaimin Muhaimin (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2022)
Online games are a new type of game that appears in the current Android era. This game is different from games in the previous era, which were usually only played at certain times, namely during the day, at night, or during school holidays. Meanwhile, online games can be played at any time, when someone holds an android. Therefore, this game can make anyone addicted so that they forget the time to pray, recite the Koran, or study. This article focuses on examining the motives that drive teenagers to become addicted to online game games by using Sumbersari Village as a case study. The results of the study show that what drives the motives of the teenagers include boredom, following trends, parents who are too free, and maximum facilities